Surgical workspace in porcine thoracoscopy with two-lung ventilation - Willem van Weteringen; Jan-Wiebe H. Korstanje; Lonneke M. Staals; Patricia A.C. Specht; Egbert G. Mik; René M.H. Wijnen; John Vlot (PLoS ONE, 2025)
In neonatal and pediatric thoracoscopy, two-lung ventilation is often used due to the size constraints of double-lumen tubes or selective bronchial blockers. Reducing the volume of both lungs to create surgical workspace requires moderation in the application of capnothorax insufflation pressures, and requires experienced anesthesiologists to manage ventilation. This balance was investigated in anesthetized pigs in the left decubitus position with a capnothorax, using volume-guaranteed intermittent positive pressure ventilation. End-expiratory computed tomography scans were obtained in 10 pigs (median weight 21.5 kg, range 17.8 to 26.3 kg) during incremental CO2 insufflation pressures of 0, 3, 5, 6, 8 and 10 mmHg. Capnothorax, right lung and left lung volumes were measured. At an insufflation pressure of 10 mmHg, peak ventilation pressures had a median of 35 cmH2O. Insufflation pressures ≥ 6 mmHg had profound cardiorespiratory effects, requiring inotropic support. Capnothorax volume reached a median of 1503 (IQR 1465–1596) ml at 10 mmHg, at which diaphragmatic displacement contributed 79.5% to capnothorax volume, with smaller contributions from lung volume (16.1%) and thoracic expansion (4.4%). Thoracoscopic workspace during two-lung ventilation originates mainly from diaphragmatic displacement. In a porcine model the marked cardiorespiratory consequences of insufflation emphasized the need to minimize insufflation pressures.